2016
DOI: 10.1037/tra0000094
|View full text |Cite
|
Sign up to set email alerts
|

Stability and transitions in posttraumatic growth trajectories among cancer patients: LCA and LTA analyses.

Abstract: The majority of transitions between different adaptation profiles occurred between 6 and 12 months after treatment. These findings offer theoretical and practice implications regarding posttraumatic growth in breast-cancer patients by distinguishing between profiles of adaptation and highlights a previously unidentified profile-struggling growth. These results contribute to the theoretical understanding of the complex relationship between growth, distress, and coping. (PsycINFO Database Record

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
62
2

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 29 publications
(67 citation statements)
references
References 44 publications
3
62
2
Order By: Relevance
“…The transitions found were mainly characterized by three paths: from struggling at 8 months to resilient at 20 months, and from thriving at 8 months to either the resilient or struggling at 20 months. In line with the findings from previous studies (Chen & Wu, 2017;Pat-Horenczyk et al, 2016), distinct classes of postdisaster adjustment based on PTSS and PTG were identified. More than half of child and adolescent survivors were classified in a class with mild PTSS and a moderate level of PTG, which was referred to as the thriving class, indicating that the survivors in this group went beyond the original level of psychosocial functioning and grew vigorously (O'Leary & Ickovics, 1994).…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…The transitions found were mainly characterized by three paths: from struggling at 8 months to resilient at 20 months, and from thriving at 8 months to either the resilient or struggling at 20 months. In line with the findings from previous studies (Chen & Wu, 2017;Pat-Horenczyk et al, 2016), distinct classes of postdisaster adjustment based on PTSS and PTG were identified. More than half of child and adolescent survivors were classified in a class with mild PTSS and a moderate level of PTG, which was referred to as the thriving class, indicating that the survivors in this group went beyond the original level of psychosocial functioning and grew vigorously (O'Leary & Ickovics, 1994).…”
Section: Discussionsupporting
confidence: 88%
“…The individuals classified in the struggling class exhibited moderate PTSS and PTG, indicating that they were undergoing a struggling process, where PTSS and PTG coexisted, following the traumatic experience (Tedeschi & Calhoun, 2004). On the other hand, we did not distinguish a class with high PTSS but a mild level of PTG, similar to the "distress" class in Pat-Horenczyk et al's (2016) study. One possible reason is related to the different types of trauma experienced by the different samples.…”
Section: Discussioncontrasting
confidence: 72%
See 1 more Smart Citation
“…Most of the literature conceptualized PTG as a potential outcome following trauma, which is manifested in positive psychological changes and qualitative changes in functioning . However, others conceptualized and assessed PTG as a process of struggling in the aftermath of traumatic events and further differentiated between constructive and illusory trajectories of PTG …”
Section: Introductionmentioning
confidence: 99%
“…This ability is termed regulatory or coping flexibility (e.g., Bonanno & Burton, 2013). Indeed, PTG was found to be positively associated with coping flexibility in cross-sectional studies (Cohen & Katz, 2015;Pat-Horenczyk et al, 2016), but replicating these findings in a longitudinal study would allow for stronger causal inference.…”
Section: Introductionmentioning
confidence: 99%